A dual-curing long-lasting durable dental self-adhesive resin cement and a preparation method thereof

CN122973276APending Publication Date: 2026-10-27AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611193452.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

具体地,针对现有自粘接树脂水门汀因采用短碳链稀释剂导致长期粘接强度不足、耐老化性差、粘接耐久性弱的问题,本发明提供一种新型自粘接树脂水门汀,通过优化稀释剂组分结构,在保证材料初期粘接性能、施工性能与体系相容性的前提下,显著提升水门汀在口腔环境下的长期粘接强度与耐老化能力,延长临床使用周期

Benefits of technology

相较于传统采用C2~C8短碳链稀释剂的自粘接树脂水门汀,本发明提供的双固化长效耐久齿科自粘接树脂水门汀具备以下显著优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The application provides a dual-curing long-acting and durable dental self-adhesive resin cement and a preparation method thereof. The dual-curing long-acting and durable dental self-adhesive resin cement comprises an A component and a B component. The A component comprises the following components in percentage by weight: a base resin, an adhesive monomer, a hydrophilic diluent monomer, an inorganic filler, an initiator and a polymerization inhibitor. The B component comprises the following components in percentage by weight: a base resin, a short carbon diluent monomer, an inorganic filler, an initiator and a polymerization inhibitor. At least one of the A component and the B component contains a (methyl) alkyl acrylate diluent with a carbon chain length greater than or equal to 10. The dental self-adhesive resin cement provided by the application can reduce the water absorption of the resin base, inhibit the hydrolysis of the adhesive interface, and improve the bonding strength and durability of the cement after cold and hot cycles and long-term saliva immersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dental and oral restoration materials technology, and relates to a dual-curing, long-lasting, durable dental self-adhesive resin cement and its preparation method. Background Technology

[0002] Self-adhesive resin cement is a core material used in dental clinics for bonding and fixing teeth and restorations. It does not require pre-etching of the tooth surface and can effectively bond with hard tooth tissues and metal / ceramic restorations by virtue of its acidic bonding monomers. It is characterized by simple operation and high clinical efficiency and is widely used in dental crowns, inlays, posts and cores and other oral restoration scenarios.

[0003] Currently, most mainstream self-adhesive resin cements on the market use short-chain diluent monomers (carbon chain length C2~C8) as the system diluent. These monomers are mostly hydrophilic or amphiphilic in structure, and have good compatibility with acidic adhesive monomers and polar resin matrices in the system. They can effectively adjust the viscosity of the system and improve the workability, making them the most common technical choice in this field.

[0004] Existing publicly available technologies (including patents and mainstream products on the market) all use short-chain acrylate monomers as diluents, combined with methacrylate matrix resins, phosphate ester self-adhesive monomers, inorganic fillers, and initiation systems to prepare self-adhesive resin cements. This relies on the high polarity of the short-chain monomers to ensure initial bonding performance and system uniformity, making it the currently common formulation system in the industry.

[0005] However, existing self-adhesive resin cements using short carbon chain diluents with carbon chain lengths of C2 to C8 have significant long-term defects, as follows: (1) Short carbon chain monomers have strong hydrophilic properties. Under the complex oral environment (long-term immersion in saliva, alternating acid and alkali, hot and cold cycles, and chewing mechanical stress), the resin matrix of the finished cement easily absorbs water and swells. The bonding interface continuously undergoes hydrolysis reaction, gradually producing microleakage.

[0006] (2) As the service time increases, the adhesive layer ages more rapidly, the adhesive strength decreases significantly, the long-term adhesive durability is poor, and clinical problems such as loosening and falling off of the restoration are likely to occur.

[0007] (3) Long-term exposure of hydrophilic components to oral media can reduce the overall aging resistance of the material, shorten the service life of the restoration, and increase the probability of patients needing follow-up visits and secondary restorations. At the same time, the high polarity of short-chain diluents can increase the overall water absorption rate of the bonding system to a certain extent, accelerate the degradation and loss of acidic bonding monomers, further weaken the stability of the interfacial bonding, and make it difficult to meet the requirements of long-term stability of the bonding effect in oral restorations.

[0008] Therefore, in this field, there is a desire to develop a dental self-adhesive resin cement that has long-term bonding strength and aging resistance in the oral environment, thereby extending its clinical use period. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide a dual-curing, long-lasting, durable dental self-adhesive resin cement and its preparation method. Specifically, addressing the problems of insufficient long-term bonding strength, poor aging resistance, and weak bonding durability in existing self-adhesive resin cements due to the use of short-chain diluents, the present invention provides a novel self-adhesive resin cement. By optimizing the diluent component structure, while ensuring the initial bonding performance, workability, and system compatibility of the material, the long-term bonding strength and aging resistance of the cement in the oral environment are significantly improved, extending its clinical service life.

[0010] The dental self-adhesive resin cement provided by this invention reduces the overall water absorption rate of the bonding system, inhibits the hydrolysis reaction and microleakage at the bonding interface, reduces the degradation and loss of acidic bonding monomers, maintains the long-term stability of the interfacial bonding, thereby reducing the risk of long-term loosening and detachment of the restoration, improving the long-term performance of the self-adhesive resin cement, and better meeting the clinical needs of oral restoration for long-term stability of bonding effect.

[0011] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a dual-curing long-lasting durable dental self-adhesive resin cement, wherein the dual-curing long-lasting durable dental self-adhesive resin cement comprises component A (matrix component) and component B (catalytic component). Component A, by weight percentage, comprises the following components: Matrix resin 18%-28%; 0-8% diluent for (meth)acrylate alkyl esters with a carbon chain length ≥10; Adhesive monomers 6%-9%; Hydrophilic dilution monomer 2%-9%; Inorganic fillers: 56%-68%; Initiator 0.48%-1.85%; Polymerization inhibitor 0.005%-0.02%; Component B, by weight percentage, comprises the following components: Matrix resin 16%-26%; Alkyl methacrylate diluent with a carbon chain length ≥10: 0-18%; Short carbon dilution monomer 2.5%-15%; Inorganic fillers: 57%-68%; Initiator 1.01%-1.65%; Polymerization inhibitor 0.005%-0.02%; Furthermore, at least one of the components A and B contains an alkyl methacrylate diluent with a carbon chain length ≥10.

[0012] The alkyl methacrylate diluent with a carbon chain length ≥10 provided by the present invention has high hydrophobicity, wherein the high hydrophobicity refers to the material having a logP (octanol-water partition coefficient) ≥4.5.

[0013] The dental self-adhesive resin cement provided by the present invention can reduce the water absorption rate of the resin matrix, inhibit the hydrolysis of the bonding interface, and improve the bonding strength and durability of the cement after cold and heat cycles and long-term saliva immersion by introducing (meth)acrylate diluents with a carbon chain length ≥10 into component A and / or component B.

[0014] Alkyl methacrylate diluent molecules with carbon chain lengths ≥10 contain long, nonpolar alkyl side chains that are uniformly distributed within the resin cross-linking network after curing. On one hand, the low-polarity hydrocarbon chains reduce the resin surface energy, forming a continuous hydrophobic barrier and reducing water molecule hydrogen bond adsorption and penetration. On the other hand, the long alkyl chains interlock to fill the cross-linked micropores, narrowing the water diffusion channels and isolating water from contact with resin ester bonds, silane interfaces, and the bonding monomer-dentin adhesive layer, inhibiting ester bond hydrolysis, filler interface debonding, and dentin collagenase degradation. Simultaneously, the long carbon chains can harmonize the compatibility between polar bonding monomers and the hydrophobic matrix, preventing paste stratification during storage. When the carbon chain length is less than 10, the alkyl hydrophobic segments are insufficient, failing to construct a complete water-resistant network, resulting in high water absorption and poor long-term adhesive durability.

[0015] In this invention, by using a (meth)acrylate alkyl ester diluent with a carbon chain length ≥10 in combination with the adhesive monomer and the matrix resin, the problems of phase separation and uneven curing can be avoided by adjusting the ratio.

[0016] In this invention, the "dual-curing" in the "dual-curing long-lasting durable dental self-adhesive resin cement" refers to light curing and oxidation-reduction curing.

[0017] In this invention, the amount of matrix resin used in component A, by weight percentage, can be 18%, 20%, 22%, 24%, 25%, 26%, 28%, etc.

[0018] In this invention, the amount of (meth)acrylate alkyl ester diluent with a carbon chain length ≥10 in component A can be 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc., by weight percentage.

[0019] In this invention, the amount of adhesive monomer used in component A, by weight percentage, can be 6%, 7%, 8%, 9%, etc.

[0020] In this invention, the amount of hydrophilic diluent monomer used in component A, by weight percentage, can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc.

[0021] In this invention, the amount of inorganic filler in component A, by weight percentage, can be 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, etc.

[0022] In this invention, the amount of initiator in component A, by weight percentage, can be 0.48%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.85%, etc.

[0023] In this invention, the amount of polymerization inhibitor in component A, by weight percentage, can be 0.005%, 0.006%, 0.008%, 0.01%, 0.012%, 0.014%, 0.015%, 0.016%, 0.018%, 0.02%, etc.

[0024] In this invention, the amount of matrix resin used in component B, by weight percentage, can be 16%, 17%, 18%, 20%, 22%, 24%, 25%, 26%, etc.

[0025] In this invention, the amount of (meth)acrylate alkyl ester diluent with a carbon chain length ≥10 in component B can be 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18%, etc., by weight percentage.

[0026] In this invention, the amount of short carbon dilution monomer used in component B, by weight percentage, can be 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 13%, 14%, 15%, etc.

[0027] In this invention, the amount of inorganic filler in component B, by weight percentage, can be 57%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, etc.

[0028] In this invention, the amount of initiator in component B, by weight percentage, can be 1.01%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.65%, etc.

[0029] In this invention, the amount of polymerization inhibitor in component B, by weight percentage, can be 0.005%, 0.006%, 0.008%, 0.01%, 0.012%, 0.014%, 0.015%, 0.016%, 0.018%, 0.02%, etc.

[0030] Preferably, both component A and component B contain alkyl (meth)acrylate diluents with a carbon chain length ≥10. When this type of long-carbon diluent is added to both component A and component B simultaneously, the hydrophobic structure of the overall cross-linked network after curing is fully covered, resulting in optimal durability performance.

[0031] Preferably, the (meth)acrylate alkyl ester diluent with a carbon chain length ≥10 is a (meth)acrylate alkyl ester diluent with a carbon chain length of C10~C18. When the carbon chain length is C10~C18, the hydrophobicity of the diluent monomer is moderate, which can take into account both system compatibility and hydrophobic anti-aging effect.

[0032] Preferably, the alkyl methacrylate diluent with a carbon chain length ≥10 includes decyl methacrylate (…). ), lauryl methacrylate ( ), tetradecyl methacrylate ( ( ), hexadecyl methacrylate, octadecyl methacrylate, any one or a combination of at least two of them.

[0033] Preferably, the adhesive monomer is a polymerizable methacrylic acid monomer containing phosphate, phosphonic acid or carboxylic acid functional groups, including any one or a combination of at least two of 10-methacryloyloxydecyl phosphate (MDP), 2-methacryloyloxyethyl phosphate, 6-methacryloyloxyhexyl phosphate, bis(2-methacryloyloxyethyl) phosphate, 3-methacryloyloxypropylphosphonic acid, 4-methacryloyloxyethyl trimellitic anhydride (4-META), and 2-methacryloyloxysuccinic acid.

[0034] Preferably, the hydrophilic diluting monomer comprises hydroxyethyl methacrylate (HEMA).

[0035] Preferably, the initiator in component A includes a photoinitiator and a reducing agent, but does not contain an oxidizing agent.

[0036] Preferably, the photoinitiator includes a primary photoinitiator and an amine-based photoco-initiator.

[0037] Preferably, the primary photoinitiator comprises any one or a combination of at least two of camphorquinone (CQ), 1-phenyl-1,2-propanedione, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, isopropylthioxanone, and 2-chlorothioxanone.

[0038] Preferably, the amine photoinitiator comprises any one or a combination of at least two of the following: dimethylaminoethyl methacrylate (DMAEMA), diethylaminoethyl methacrylate, dihydroxyethylaminoethyl methacrylate, ethyl 4-dimethylaminobenzoate, methyl 4-dimethylaminobenzoate, N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, 4-N,N-dimethylaminophenylethanol, triethanolamine, and N-methyldiethanolamine.

[0039] Preferably, the photoinitiator is a compound of camphorquinone and dimethylaminoethyl methacrylate.

[0040] Preferably, the reducing agent comprises any one or a combination of at least two of N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, N,N-dimethylaniline, N,N-diethyl-p-toluidine, N,N-dimethyl-o-toluidine, N,N-dimethyl-m-toluidine, 4-N,N-dimethylaminophenylethanol, p-dimethylaminobenzaldehyde, ethyl 4-dimethylaminobenzoate, methyl 4-dimethylaminobenzoate, N-methyldiethanolamine, triethanolamine, acetylthiourea, propionylthiourea, benzoylthiourea, phenylthiourea, diphenylthiourea, trifluoromethylphenylthiourea, barbituric acid, sodium 1,3-dimethylbarbiturate, ascorbic acid, sodium ascorbate, copper acetylacetonate (II), and vanadium acetylacetonate (IV).

[0041] Preferably, the initiator in component B includes an oxidant and does not contain a photoinitiator or a reducing agent. That is, the initiation system in this invention is a photoinitiation system and a redox initiation system.

[0042] Preferably, the oxidizing agent includes any one or a combination of at least two of the following: benzoyl peroxide (BPO), p-chlorobenzoyl peroxide, o-methylbenzoyl peroxide, m-methylbenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, isobutyryl peroxide, isooctyl peroxide, tert-butyl cumene peroxide, di-tert-butyl peroxide, cumene hydroperoxide (CHP), and stearyl peroxide.

[0043] Preferably, the short carbon diluent monomer comprises triethylene glycol dimethacrylate (TEGDMA).

[0044] Preferably, the matrix resins in components A and B each independently comprise bisphenol A dimethacrylate (Bis-GMA) and / or bisphenol A-ethoxylated glycidyl dimethacrylate (Bis-EMA).

[0045] Preferably, the inorganic fillers in components A and B each independently comprise silane-modified glass powder and / or hydrophobic fumed silica.

[0046] Preferably, the silane-modified glass powder includes any one or a combination of at least two of silane-modified barium aluminum borosilicate glass powder, silane-modified fluorine aluminum barium glass powder, silane-modified strontium borosilicate glass powder, and silane-modified lanthanum borosilicate glass powder, with silane-modified barium aluminum borosilicate glass powder being the most preferred.

[0047] Preferably, the average particle size of the silane-modified glass powder is 0.5μm to 5μm, such as 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., and more preferably 2μm.

[0048] Preferably, the polymerization inhibitors in both component A and component B include 2,6-di-tert-butyl-p-cresol (BHT).

[0049] Preferably, component A further includes a colorant.

[0050] Preferably, the content of the pigment is 0.01%-0.1% based on the total weight of component A as 100%, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.08%, 0.1%, etc.

[0051] Preferably, component B further includes a colorant.

[0052] Preferably, the content of the pigment is 0.01%-0.1% based on the total weight of component B as 100%, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.08%, 0.1%, etc.

[0053] Preferably, the colorants in both component A and component B include titanium oxide.

[0054] As a preferred technical solution of the present invention, the dual-curing long-lasting durable dental self-adhesive resin cement includes component A and component B; Component A, by weight percentage, comprises the following components: Matrix resin 18%-28%; 3%-8% of (meth)acrylate alkyl ester diluents with a carbon chain length ≥10; Adhesive monomers 6%-9%; Hydrophilic dilution monomer 2%-9%; Inorganic fillers: 56%-68%; Initiator 0.48%-1.85%; Polymerization inhibitor 0.005%-0.02%; Pigment content: 0.01%-0.1%; Component B, by weight percentage, comprises the following components: Matrix resin 16%-26%; 8%-18% diluent for (meth)acrylates with a carbon chain length ≥10; Short carbon dilution monomer 2.5%-15%; Inorganic fillers: 57%-68%; Initiator 1.01%-1.65%; Polymerization inhibitor 0.005%-0.02%; Pigment content: 0.01%-0.1%.

[0055] Preferably, the mass ratio of component A to component B is (0.8-1.2):1, such as 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, etc. Under this ratio, the content matching degree of photoinitiating component, reducing agent and oxidizing agent of redox system in the system is optimal, and efficient photocuring and stable chemical curing can be achieved simultaneously.

[0056] In a second aspect, the present invention provides a method for preparing a dual-curing, long-lasting, durable dental self-adhesive resin cement as described in the first aspect, the method comprising the following steps: (1) Mix the matrix resin, optional alkyl methacrylate diluent with a carbon chain length ≥10, adhesive monomer, hydrophilic diluent monomer, inorganic filler, initiator, polymerization inhibitor, and optional colorant in the formula amount evenly, and remove bubbles under vacuum to obtain component A. (2) Mix the matrix resin, optional alkyl methacrylate diluent with a carbon chain length ≥10, short carbon diluent monomer, inorganic filler, initiator, polymerization inhibitor, and optional colorant in the formula amount evenly, and remove bubbles under vacuum to obtain component B. (3) Seal and fill components A and B separately into a two-component dental injection tube in a light-proof environment; (4) When using, mix component A and component B to obtain the dual-curing long-lasting durable dental self-adhesive resin cement; Wherein, at least one of the components A and B contains an alkyl methacrylate diluent with a carbon chain length ≥10.

[0057] Compared with the prior art, the present invention has the following beneficial effects: Compared to traditional self-adhesive resin cements that use C2-C8 short-chain diluents, the dual-curing, long-lasting, durable dental self-adhesive resin cement provided by this invention has the following significant advantages: (1) Low water absorption and low solubility: The water absorption of traditional short-chain diluent systems is ≥28μg / mm 3 The water absorption value of this invention is ≤20μg / mm 3 Traditional system solubility value ≥2μg / mm 3 The solubility value of this invention is ≤1 μg / mm 3 The hydrophobic structure effectively prevents moisture from penetrating the resin matrix and the bonding interface.

[0058] (2) The bonding strength and long-term durability are greatly improved. Initial bond strength (dentin bonding): The present invention is basically the same as the prior art, reaching 22~26MPa, ensuring the initial bond effect in clinical practice; Bond strength after long-term aging: After aging tests, the bond strength of traditional products decreases to 10~13.1MPa, and the bond strength retention rate is less than 55%; the bond strength of the present invention remains at 15~22 MPa after aging, with a strength retention rate of not less than 65%, preferably higher than 75%, and excellent long-term bond stability.

[0059] (3) Inhibit microleakage Oral microleakage rating test: Traditional short carbon chain systems have high microleakage levels after aging and are prone to gap leakage; the present invention significantly reduces the microleakage level due to effective inhibition of interfacial hydrolysis, thereby reducing the risk of secondary caries and loosening of restorations.

[0060] All of the above performance tests were conducted in accordance with the dental resin cement industry standard. The test conditions were: constant temperature 37℃ water bath immersion and hot and cold cycling (5℃~55℃, 10,000 cycles) to simulate the oral aging environment.

[0061] In summary, without sacrificing initial performance and operability, this invention completely improves the defects of long-term aging and bonding failure of existing products, and significantly extends the service life of self-adhesive resin cement. Detailed Implementation

[0062] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0063] Example 1 This embodiment provides a dual-curing long-lasting durable dental self-adhesive resin cement, which includes component A (matrix component) and component B (catalytic component). The formulation of component A is shown in Table 1, where the amount of each component is expressed as a weight percentage (%). The formulation of component B is shown in Table 2, where the amount of each component is expressed as a weight percentage (%).

[0064] The preparation method includes the following steps: (1) Mix the matrix resin, alkyl methacrylate diluent with a carbon chain length ≥10, adhesive monomer, hydrophilic diluent monomer, inorganic filler, initiator, polymerization inhibitor and colorant in the formula amount evenly, and remove bubbles under vacuum to obtain component A; (2) Mix the matrix resin, alkyl methacrylate diluent with a carbon chain length ≥10, short carbon diluent monomer, inorganic filler, initiator, polymerization inhibitor and colorant in the formula amount evenly, and remove bubbles under vacuum to obtain component B; (3) Seal and fill components A and B separately into a two-component dental injection tube in a light-proof environment; (4) When using, mix component A and component B at a mass ratio of 1:1 to obtain the dual-curing long-lasting durable dental self-adhesive resin cement.

[0065] Examples 2-5, Comparative Examples 1-2 The only difference from Example 1 is that components A and / or B are different, as shown in Tables 1 and 2.

[0066] Table 1 Table 2 The silane-modified barium aluminum borosilicate glass powder (average particle size of 2 μm) in Tables 1 and 2 was purchased from Schott.

[0067] The performance of the self-adhesive resin cement provided in the embodiments and comparative examples of the present invention was tested using the following methods: (1) Initial bond strength, bond strength after thermal cycling aging, and microleakage level after aging: Tested according to YY / T0519-2022 "Dentistry and Testing of Bonding of Tooth Structures"; The criteria for evaluating the microleakage level after aging are as follows: No penetration = Level 0; The portion of tooth enamel that has seeped into the cavity wall = Grade 1; Penetrating into the dentin within the cavity wall but not reaching the pulp floor = Grade 2; Penetration to the bottom of the cavitary marrow = Level 3.

[0068] (2) Tests on water absorption and solubility of materials: Tests were conducted in accordance with YY 1042-2023 "Polymer-based restorative materials for dentistry".

[0069] (3) Stability of the two-component product during 6 months of storage: The method of external light protection storage observation commonly used in the domestic dental resin material industry was adopted.

[0070] (4) Bond strength retention rate = Bond strength after thermal cycling aging / Initial bond strength × 100%.

[0071] The performance test results are shown in Table 3.

[0072] Table 3 As can be seen from Table 3: (1) The initial bond strength values ​​of the samples provided in the examples and comparative examples are similar, which proves that alkyl methacrylate diluents with a carbon chain length ≥10 do not impair the initial clinical bond performance of the materials.

[0073] (2) No alkyl methacrylate diluent with a carbon chain length ≥10 was added to Comparative Example 1, while Comparative Example 2 used only a diluent monomer with a carbon chain length of 8. After cold and hot cycling aging, the bonding strength decreased significantly, the water absorption value and solubility value increased significantly, and microleakage was serious. This proves that diluents with a carbon chain length <10 cannot form an effective hydrophobic barrier.

[0074] (3) Examples 1-3, in which components A and B are simultaneously added with alkyl methacrylate diluents with a carbon chain length ≥10, exhibit the best hydrophobic durability; among them, Example 3, in which diluents with a carbon chain length of 12 and diluents with a carbon chain length of 18 are combined, has the lowest water absorption rate and the highest retention rate of aging bond strength.

[0075] (4) Compared with Comparative Example 1 and Comparative Example 2, Examples 4 and 5 (only one component with carbon chain length ≥10 added) showed significant improvements in water absorption, bonding strength after thermal cycling aging, and microleakage. This proves that the invention's definition of "at least one of component A and component B contains carbon chain length ≥10 (meth)acrylate diluent" is feasible and has an improvement effect.

[0076] The durability of Examples 1-3 (with both components A and B having alkyl methacrylate diluents with a carbon chain length ≥10) is significantly better than that of Examples 4 and 5, which have only one component added. This proves that "both components A and B contain alkyl methacrylate diluents with a carbon chain length ≥10" is the preferred technical solution of the present invention.

[0077] In summary, the self-adhesive resin cement provided by this invention, by limiting at least one of components A and B to contain an alkyl methacrylate diluent with a carbon chain length ≥10, significantly reduces the material's water absorption rate and inhibits hydrolysis at the bonding interface without sacrificing initial bonding strength or workability. This results in improved bonding strength and durability after long-term thermal cycling, bringing unexpected technical effects.

[0078] The applicant declares that this invention illustrates the dual-curing, long-lasting, durable dental self-adhesive resin cement and its preparation method through the above embodiments. However, this invention is not limited to the above embodiments, meaning that this invention does not necessarily rely on the above embodiments for implementation. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of the raw materials used, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of this invention.

Claims

1. A dual-curing, long-lasting, durable dental self-adhesive resin cement, characterized in that, The dual-curing long-lasting durable dental self-adhesive resin cement comprises component A and component B; Component A, by weight percentage, comprises the following components: Matrix resin 18%-28%; 0-8% diluent for (meth)acrylate alkyl esters with a carbon chain length ≥10; Adhesive monomers 6%-9%; Hydrophilic dilution monomer 2%-9%; Inorganic fillers: 56%-68%; Initiator 0.48%-1.85%; Polymerization inhibitor 0.005%-0.02%; Component B, by weight percentage, comprises the following components: Matrix resin 16%-26%; Alkyl methacrylate diluent with a carbon chain length ≥10: 0-18%; Short carbon dilution monomer 2.5%-15%; Inorganic fillers: 57%-68%; Initiator 1.01%-1.65%; Polymerization inhibitor 0.005%-0.02%; Furthermore, at least one of the components A and B contains an alkyl methacrylate diluent with a carbon chain length ≥10.

2. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to claim 1, characterized in that, Both component A and component B contain alkyl methacrylate diluents with a carbon chain length ≥10; Preferably, the alkyl methacrylate diluent with a carbon chain length ≥10 is an alkyl methacrylate diluent with a carbon chain length of C10~C18; Preferably, the alkyl methacrylate diluent with a carbon chain length ≥10 includes any one or a combination of at least two of decyl methacrylate, lauryl methacrylate, tetradecyl methacrylate, hexadecyl methacrylate, and octadecyl methacrylate.

3. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to claim 1 or 2, characterized in that, The adhesive monomer is a polymerizable methacrylic acid monomer containing phosphate, phosphonic acid or carboxylic acid functional groups, including any one or a combination of at least two of 10-methacryloyloxydecyl phosphate, 2-methacryloyloxyethyl phosphate, 6-methacryloyloxyhexyl phosphate, bis(2-methacryloyloxyethyl) phosphate, 3-methacryloyloxypropylphosphonic acid, 4-methacryloyloxyethyl trimellitic anhydride, and 2-methacryloyloxysuccinic acid. Preferably, the hydrophilic diluting monomer comprises hydroxyethyl methacrylate.

4. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to any one of claims 1-3, characterized in that, The initiator in component A includes a photoinitiator and a reducing agent; Preferably, the photoinitiator includes a primary photoinitiator and an amine-based photoco-initiator; Preferably, the primary photoinitiator comprises any one or a combination of at least two of camphorquinone, 1-phenyl-1,2-propanedione, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, isopropylthioxanone, and 2-chlorothioxanone; Preferably, the amine photoinitiator comprises any one or a combination of at least two of the following: dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, dihydroxyethylaminoethyl methacrylate, ethyl 4-dimethylaminobenzoate, methyl 4-dimethylaminobenzoate, N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, 4-N,N-dimethylaminophenylethanol, triethanolamine, and N-methyldiethanolamine. Preferably, the photoinitiator is a compound of camphorquinone and dimethylaminoethyl methacrylate; Preferably, the reducing agent comprises any one or a combination of at least two of N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, N,N-dimethylaniline, N,N-diethyl-p-toluidine, N,N-dimethyl-o-toluidine, N,N-dimethyl-m-toluidine, 4-N,N-dimethylaminophenylethanol, p-dimethylaminobenzaldehyde, ethyl 4-dimethylaminobenzoate, methyl 4-dimethylaminobenzoate, N-methyldiethanolamine, triethanolamine, acetylthiourea, propionylthiourea, benzoylthiourea, phenylthiourea, diphenylthiourea, trifluoromethylphenylthiourea, barbituric acid, sodium 1,3-dimethylbarbiturate, ascorbic acid, sodium ascorbate, copper acetylacetonate (II), and vanadium acetylacetonate (IV).

5. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to any one of claims 1-4, characterized in that, The initiator in component B includes an oxidant; Preferably, the oxidizing agent includes any one or a combination of at least two of the following: benzoyl peroxide, p-chlorobenzoyl peroxide, o-methylbenzoyl peroxide, m-methylbenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, isobutyryl peroxide, isooctyl peroxide, tert-butyl cumene peroxide, di-tert-butyl peroxide, cumene hydroperoxide, and stearyl peroxide.

6. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to any one of claims 1-5, characterized in that, The short carbon diluent monomer includes triethylene glycol dimethacrylate.

7. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to any one of claims 1-6, characterized in that, The matrix resins in components A and B each independently comprise bisphenol A dimethacrylate and / or bisphenol-A-ethoxylated glycidyl dimethacrylate.

8. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to any one of claims 1-7, characterized in that, The inorganic fillers in components A and B each independently include silane-modified glass powder and / or hydrophobic fumed silica. Preferably, the silane-modified glass powder includes any one or a combination of at least two of silane-modified barium aluminum borosilicate glass powder, silane-modified fluoroaluminum barium glass powder, silane-modified strontium borosilicate glass powder, and silane-modified lanthanum borosilicate glass powder, with silane-modified barium aluminum borosilicate glass powder being the most preferred. Preferably, the average particle size of the silane-modified glass powder is 0.5 μm to 5 μm; Preferably, the polymerization inhibitors in both component A and component B include 2,6-di-tert-butyl-p-cresol; Preferably, component A further includes a colorant; Preferably, the pigment content is 0.01%-0.1% based on the total weight of component A as 100%; Preferably, component B further includes a colorant; Preferably, the pigment content is 0.01%-0.1% based on the total weight of component B as 100%; Preferably, the colorants in both component A and component B include titanium oxide.

9. The dual-curing, long-lasting, durable dental self-adhesive resin cement according to any one of claims 1-8, characterized in that, The dual-curing long-lasting durable dental self-adhesive resin cement comprises component A and component B; Component A, by weight percentage, comprises the following components: Matrix resin 18%-28%; 3%-8% of (meth)acrylate alkyl ester diluents with a carbon chain length ≥10; Adhesive monomers 6%-9%; Hydrophilic dilution monomer 2%-9%; Inorganic fillers: 56%-68%; Initiator 0.48%-1.85%; Polymerization inhibitor 0.005%-0.02%; Pigment content: 0.01%-0.1%; Component B, by weight percentage, comprises the following components: Matrix resin 16%-26%; 8%-18% diluent for (meth)acrylates with a carbon chain length ≥10; Short carbon dilution monomer 2.5%-15%; Inorganic fillers: 57%-68%; Initiator 1.01%-1.65%; Polymerization inhibitor 0.005%-0.02%; Pigment content: 0.01%-0.1%; Preferably, the mass ratio of component A to component B is (0.8-1.2):

1.

10. A method for preparing a dual-curing, long-lasting, durable dental self-adhesive resin cement as described in any one of claims 1-9, characterized in that, The preparation method includes the following steps: (1) Mix the matrix resin, optional alkyl methacrylate diluent with a carbon chain length ≥10, adhesive monomer, hydrophilic diluent monomer, inorganic filler, initiator, polymerization inhibitor, and optional colorant in the formula amount to obtain component A; (2) Mix the matrix resin, optional alkyl methacrylate diluent with a carbon chain length ≥10, short carbon diluent monomer, inorganic filler, initiator, polymerization inhibitor, and optional colorant in the formula amount to obtain component B; (3) Seal and fill components A and B separately into a two-component dental injection tube in a light-proof environment; (4) When using, mix component A and component B to obtain the dual-curing long-lasting durable dental self-adhesive resin cement; Wherein, at least one of the components A and B contains an alkyl methacrylate diluent with a carbon chain length ≥10.